2023
DOI: 10.1038/s41598-023-34997-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cytotoxicity on human lung cancer cells and DNA binding stratagem of camptothecin functionalised silver nanoparticles through multi-spectroscopic, and calorimetric approach

Abstract: The influence of nanoparticles inside the human body and their interactions with biological macromolecules need to be explored/studied prior to specific applications. The objective of this study is to find the potential of camptothecin functionalised silver nanoparticles (CMT-AgNPs) in biomedical applications. This article primarily investigates the binding stratagem of CMT-AgNPs with calf thymus DNA (ctDNA) through a series of spectroscopic and calorimetric methods and then analyses the anticancer activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…As previously mentioned, the majority of research regarding NPs in the context of in vitro lung models is in relation to their toxicity or potential as therapeutics. 178–181 While the use of NPs as contrast agents is quite common in in vivo studies, 182–184 few studies recognize their utility as agents to characterize and functionalize lung in vitro 3D models. Characterizing these models and evaluating the effect of different therapeutics is particularly challenging given their complex architecture, which can pose penetration depth limits and hamper the diffusion of labels, antibodies or dyes, and the ability to follow their evolution over time.…”
Section: Nanoparticles As Stimuli Responsive Actuators To Create Dyna...mentioning
confidence: 99%
“…As previously mentioned, the majority of research regarding NPs in the context of in vitro lung models is in relation to their toxicity or potential as therapeutics. 178–181 While the use of NPs as contrast agents is quite common in in vivo studies, 182–184 few studies recognize their utility as agents to characterize and functionalize lung in vitro 3D models. Characterizing these models and evaluating the effect of different therapeutics is particularly challenging given their complex architecture, which can pose penetration depth limits and hamper the diffusion of labels, antibodies or dyes, and the ability to follow their evolution over time.…”
Section: Nanoparticles As Stimuli Responsive Actuators To Create Dyna...mentioning
confidence: 99%
“…Camptothecin [CPT, (4S)-4-Ethyl-4-hydroxy-1H-pyrano[3 0 ,4 0 :6,7]indolizino[1,2-b]quinoline-3,14(4H,12H)-dione], an indole alkaloid characterized by a pentacyclic structure, is primarily derived from Camptotheca acuminata (Schultz, 1973). Several studies have shown that CPT and its derivatives can inhibit the progression of malignancies, including breast, cervical, lung, and liver cancers (Ali et al, 2023;Hou et al, 2023;Raj et al, 2023). Mechanistic investigations have elucidated that CPT forms covalent complexes with topoisomerase I (TOPO I) and DNA, thereby inhibiting DNA re-ligation, leading to DNA strand breaks, and consequently inducing apoptosis, which are promising features of cancer therapeutics (Tesauro et al, 2019;Thomas & Pommier, 2019).…”
Section: Camptothecinmentioning
confidence: 99%
“…AgNPs have shown promise as potential anticancer agents due to their ability to induce apoptosis (cell death) in cancer cells. Additionally, AgNPs have been shown to have low toxicity towards normal cells, making them a potential alternative to conventional chemotherapy drugs [ 21 , 22 , 23 ]. AgNPs have been investigated as potential drug delivery vehicles due to their small size and unique physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%